A case‐study approach to mapping Corporate Citizenship. (24th August 2022) - Homer, Stephen T.
Abstract: This explores what responsible business practice within the context of Malaysia, an Eastern collective society, diverging from the Western individualistic society where most Corporate Social Responsibility (CSR) research originates. A bottom‐up approach was adopted, incorporating different stakeholder perspectives of a case‐study firm, widely acknowledged for its CSR programs. Concept mapping method was selected because it is a structural conceptualization method designed to organize and represent ideas from an identified group adding structure to disorganized and subjective ideas. By using concept mapping all the various perspectives and ideas were brought together to create a single conceptualization. The findings from the concept mapping present 101 statements which produced seven clusters; Products & Services, Community Oriented, Stakeholder & Business Value, Employee Oriented, Legal & Ethical Responsibilities, Environmental & Social Oriented, and Philanthropic Oriented. These clusters covered the whole conceptual domain of Corporate Citizenship and demonstrated multiple CSR theories, including corporate sustainability, stakeholder concept, and shared value, were apparent, while also uncovering some unique aspects from the normative stakeholder perspective. The implications of this study suggest that while some aspects of globally institutionalized CSR are generically accepted, there are contextually specific aspects which need to be considered as these may contradict or conflict with the "global" standards.